Bolivarian Republic of Venezuela : Investing in Human Capital for Growth, Prosperity, and Poverty Reduction - World Bank (Washington, DC, 2013)
This report draws on limited, available data to analyze selected economic, and social issues, which include better understanding of poverty, and inequality in relation to real income, and, improving the allocation of social expenditures, while increasing the effectiveness of social programs. The deterioration of social, and human capital should be prevented, by simultaneously promoting its accumulation. The report reviews the dismal economic performance of the country over the last decade, where the inability of policymakers to cope with the oil cycles, and prices decline prevails. Moreover, the country's dependence on the oil sector has deepened, while the share of agriculture, and manufacturing decreased, aggravated by the lack of export diversification, and the negative impact of the overvalued domestic currency on external competitiveness. Not surprisingly, labor productivity also decreased, reflecting a low real economic growth, which results in higher unemployment, poverty and inequality increases. The needed acceleration of human, and social capital development focuses on education, health, and the decline of crime and violence, suggesting continued implementation of primary education reforms, through the development of new curriculum, improved quality of basic education, and educational financing. Health recommendations include efficient resource allocation, prioritization of high-impact programs, and expanded private participation, and institutional development.